Moda nascida póstuma: os modos simbólicos da roupa que não existe - Winck, Lucas Bitencourt da Costa (Universidade do Vale do Rio dos Sinos, 2020)
This work proposes a discussion about the symbolic relations of fashion and the modes acquired by it in postmodernity, understanding the sociocultural developments that incline fashion towards a posthumous conformation. For this, an analysis of the symbolic antecedents of clothing takes place, tracing the act of dressing to reach the end, to the possible echoes of postmodernity, such as, for exemple, the society of the spectacle, resulting in a questioning about the insufficiency of the phenomenon, which suggest a possible death, followed by a possible later existence, a fashion that is born posthumously. The final objective of this work is the development of a non-collection, inspired by Martin Margiela's enigmatic modus operandi and by the spectral notions of the postmodern moment.
Keywords: Moda; Pós-modernidade; Simbólico; Espetacularização; Morte da moda; Moda póstuma; Fashion; Postmodernity; Symbolic; Spectacularization; Death of fashion; Posthumous fashion